Analisis C-Type Lectin - Iman Supriatna (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2015)
This study aimed to determine the diversity of c-type lectin on the various groups of species based on data contained in National Center for Biotechnology Information (NCBI). The method used is a bioinformatics study by analyzing the amino acid molecules lectin particular type of c-type lectin found in NCBI and analyze of sequence and scores of c-type lectin with Prosite analysis based. The results showed that the data of genbank seen as the varying length of the amino acid sequence types of c-type lectin of groups of species of fish 159-304 aa, bivalves 155-524 aa, plants 349-414 aa, fungi 593-981 aa, and bacteria 564-4379 aa. Prosite analysis results with the c-type lectin on some species have slightly varied score that O. niloticus 18.010, M. meretrik 18, 112, A. thaliana and P. marinus 15,104. Potential C-type lectin on some of these species need to be analyzed further to determine the extraction technique and its benefits in the field of maritime affairs and fisheries.